Design and Feasibility Evaluation of Multimedia-Based Digital Learning Module for Women’s Body Proportion Drawing in Vocational Education - Sri Listiani; M Noerharyono; Zulfira Farah Nubua (Universitas Negeri Semarang, 2025)
This study focuses on the design and feasibility evaluation of a multimedia-based digital learning module developed to support the teaching of women’s body proportion drawing in grade X vocational education. The module was designed as an interactive digital system integrating text, images, audio, and video to enhance user engagement and independent learning. The feasibility assessment was conducted by expert panelists using a mixed closed–open questionnaire based on module characteristics, including self-instruction, self-contained, adaptive, stand-alone, and user-friendly aspects, as well as media quality elements such as format, organization, attractiveness, typography, white space, and consistency. A descriptive quantitative approach with a one-shot case study design was employed to analyze the evaluation results. The findings indicate that the module achieved a score of 90.27% for module characteristics and 92.5% for media quality elements, with an overall feasibility score of 91.44%, categorized as “very good.” These results demonstrate that the developed module meets the criteria of a well-structured and functional digital learning system that can effectively support independent learning. This study contributes to the development of applied digital learning technology in vocational education by demonstrating how multimedia-based instructional design can enhance learning accessibility and usability. The findings also provide a reference for future development of technology-integrated learning media in technical and applied educational contexts.